2009
DOI: 10.1002/ep.10390
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic hydrotreatment of fast pyrolysis oil: Model studies on reaction pathways for the carbohydrate fraction

Abstract: Fast pyrolysis oil can be upgraded by a catalytic hydrotreatment (250-4008C, 100-200 bar) using heterogeneous catalysts such as Ru/C to hydrocarbon-like products that can serve as liquid transportation fuels. Insight into the complex reaction pathways of the various component fractions during hydrotreatment is desirable to reduce the formation of by-products such as char and gaseous components. This paper deals with the catalytic hydrotreatment of representative model components for the carbohydrate fraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 36 publications
1
74
1
1
Order By: Relevance
“…In addition to hydrogenation, a thermal pathway proceeded to form hydromethylfurfural, levulinic acid and humins. Furthermore, the study demonstrated that the acetic acid added in this system increased solids formation by promoting the thermal route [42].…”
Section: Hdo Of Other Oxygenatesmentioning
confidence: 85%
“…In addition to hydrogenation, a thermal pathway proceeded to form hydromethylfurfural, levulinic acid and humins. Furthermore, the study demonstrated that the acetic acid added in this system increased solids formation by promoting the thermal route [42].…”
Section: Hdo Of Other Oxygenatesmentioning
confidence: 85%
“…Repeated use of the Ru/C catalyst in hydrotreating experiments resulted in decreased liquid yield, increased solids, a reduction in H/C and less methane in the gas phase. Hydrodeoxygenation of model bio-oil compounds were investigated by Wildschut et al [135] under conditions of 250˚C, 10 MPa for 4.3 hours with an Ru/C catalyst. Two parallel reaction pathways were observed, a thermal non-catalysed pathway and a hydrogenation pathway leading to smaller polyols and gaseous hydrocarbons such as methane and ethane.…”
Section: 212european Research In Hydroprocessingmentioning
confidence: 99%
“…Heeres et al performed fundamental studies on hydrotreatment of bio-oils and model compounds using a Ru/C catalyst [28]. Different levels of upgrading were studied from stabilisation with low levels of oxygen removal through mild hydrotreatment to two-stage hydrotreatment with substantial oxygen removal.…”
Section: Introductionmentioning
confidence: 99%